Primary Neuroendocrine Tumor of the Parotid Gland: A Case Report and a Comprehensive Review of a Rare Entity - Olga Martínez-Sáez; Javier Molina-Cerrillo; Carmen Moreno García del Real; Rafael Barberá Durban; Juan J. Díez; Teresa Alonso-Gordoa; Enrique Grande Pulido (Case Reports in Otolaryngology)
Neuroendocrine tumors (NETs) comprise a heterogeneous group of malignancies from cells derived from the neural crest with neuroendocrine differentiation. Despite the differences in the site of origin, nomenclature, biological behavior, and functional status, NETs share certain ultrastructural and immunohistochemical features. NETs are relative rare tumors with an annual incidence of 5.76 new cases per 100.000 inhabitants and they usually appear in the gastrointestinal tract or in the pulmonary system. Head and neck NETs are uncommon with limited information regarding frequency, most of them showing small cell carcinoma features. NETs that arise from the salivary glands are exceedingly rare. Regardless of their low frequency, it is imperative to accurately differentiate these tumors from the much more common squamous cell carcinomas and from metastasis from another primary tumor due to the completely different therapeutic approaches and prognosis. The diagnosis is based on the recognition of the typical neuroendocrine architecture and immunohistochemical staining and on an exhaustive work-up. Hereby, we report a case of a moderately differentiated NET of the parotid gland that was treated with a complete parotidectomy. We summarize the clues that led to the final diagnosis and major strategies that were employed to manage the patient. We also perform a comprehensive review of the scarce available literature on this topic.